Secagem e caracterização da hortelã (Mentha Spicata L.) pelo método cast-tape drying - Silva, Jaqueline Luisa (2021)
Mint (Mentha spicata L.) is a medicinal and aromatic plant with antioxidant properties, antiseptic, antifungal, diuretic and analgesic action. It can be used as seasoning in food, flavoring agent in drinks, essences, oral hygiene products and by the pharmaceutical industry for the production of medicines. Per having a high moisture content in its chemical composition, this herb is considered highly perishable, being necessary to subject it to suitable methods for its preservation. In this sense, drying is an option that can increase the shelf life of food by slowing microbial growth and biodegradation. A drying method considered promising is the cast-tape drying (CTD), capable of producing dry foods with high nutritional value. Having seen the above, the objective of this study was to investigate the drying of the mint with and without bleaching, CB and SB respectively, by CTD, aiming to analyze the effect of the process variables: circulating water temperature (55, 72.5 and 90 ° C) and thickness of the paste layer (2, 3 and 4 mm) in the characteristics of the dry material obtained. The drying condition that showed the best preservation results for the bioactive compounds of the mint was the highest temperature (90 ° C) combined with the smallest thickness (2 mm) and the use of bleaching, when compared to drying at 55 ° C and 4 mm. In this condition the final humidity of the product was close to 10%, with drying time around 20 minutes. As for the color of the mint, the smallest variation observed in relation to the wet sample was the drying condition with the lowest temperature of the circulating water (55 ° C) and intermediate thickness (3 mm) both SB and CB. In relation to hygroscopicity, it was observed that higher drying temperatures caused higher hygroscopic values and that the bleached samples showed less hygroscopic dried mints in all evaluated drying conditions. Thus, it is concluded that the drying of the mint was possible by CTD, making it an attractive option for the use of this material.